The hidden effect of normal changes in barometric pressure and humidity on track cycling pursuit performance. - Dwyer, D. (National Elite Sports Council 2009 Athlete Services Forum - High Performance Programming for Success - 11-12th November - Satellite Program - Applied Physiology Conference 2009 - Australian Institute of Sport, Canberra - 10th, 11th and 13th November, 2009)
Cycling Australia (CA) publish an automatic qualifying time for the individual pursuit that determines team selection. CA also recognise that ambient air temperature affects air density and therefore aerodynamic drag, which affects an athlete`s performance in the pursuit. To make the evaluation of officially recorded pursuit times fair, Cycling Australia publish a temperature correction factor that allows +/- 0.08s/1000m for each degree of ambient temperature below or above 20oC. However, this correction process ignores the important effects of barometric pressure and humidity, both of which vary hourly and daily and also affect air density and aerodynamic drag. The present study calculates the important effect of changes in barometric pressure and humidity on pursuit performance. Methods To illustrate the effect of variations in these environmental factors on pursuit performance, a case study approach was taken whereby a recent officially recorded 3000m pursuit performance was modelled to quantify the power output of the athlete throughout the race. Mathematical modelling was performed using published cycling specific equations that relate drag and power to velocity and therefore pursuit time 1,2. Subsequently, by keeping the power output of the athlete constant in the model, the effect of temperature, pressure and humidity on pursuit velocity can be assessed by varying these three environmental factors in a stepwise process. Results Mathematical modelling of the effect of varying ambient conditions indicates that each degree of increase in temperature above 20oC results in a decrease in pursuit time of 0.07s/1000m, each 10% increase in humidity above 50% decreases pursuit time by 0.4s/1000m and each 6.6 hPa decrease in barometric pressure increases pursuit time by 0.13s/1000m. The three environmental factors were varied within the actual range recorded each day by the BOM at 9AM and 3PM, in Melbourne throughout January 2009 (15-25oC, 0-100% RH & 966-1033 hPa). To illustrate the potential effects of changes in pressure and humidity on pursuit performance, Table 1 indicates the actual range of variation recorded for these ambient conditions and their predicted effect on pursuit time. When the actual changes in all three ambient conditions are compared, the relative magnitude of their contribution to the total change in pursuit performance is; temperature 49%, barometric pressure 37% and humidity 14%. Discussion/Conclusion The present calculation of the effect of temperature on pursuit performance is very close to that predicted by CA (0.07 vs. 0.08s/1000m). The changes in ambient temperature reported here were outdoor and would be moderated in an indoor track, but changes in pressure and humidity would not. While temperature changes account for about half of the total effect on pursuit performance, barometric pressure and humidity changes comprise the other half and therefore should not be ignored.